The effects of poor maternal nutrition during gestation on postnatal growth and development of lambs. Issue 2 (1st February 2016) - Hoffman, M. L.; Peck, K. N.; Forella, M. E.; Fox, A. R.; Govoni, K. E.; Zinn, S. A.
Abstract: Poor maternal nutrition can affect the growth and development of offspring, which may lead to negative consequences in adult life. We hypothesized that lambs born to poorly nourished ewes would have reduced growth rate and increased fat deposition, with corresponding changes in the somatotropic axis, and leptin, insulin and glucose concentrations. Ewes ( n = 36; 12/treatment) were assigned 1 of 3 diets; 100% (CON), 60% (RES), or 140% (OVER) of NRC requirements for TDN at d 31 of gestation until parturition. One lamb per ewe ( n = 35; 11 to 12 per treatment) was used; 18 lambs were euthanized at d 1, and 17 were fed the same diet for 3 mo and then euthanized. Lamb crown rump length (CRL), heart girth, BW, and BCS were measured, and blood samples were collected at d 1 and then at weekly intervals until euthanasia. Averaged from d 1 until 3 mo, lambs from OVER ewes were larger compared with lambs born to CON ewes (BW [16.97 vs. 15.44 kg ± 0.60; P = 0.09], ADG [0.23 vs. 0.21 ± 0.01 kg/d; P = 0.01], and CRL [68.9 vs. 66.1 ± 0.80 cm; P = 0.02]). On a BW basis, heart weight from lambs from RES (0.18 kg ± 0.03; P = 0.03) ewes was greater than that of CON lambs (0.15 kg ± 0.03). Backfat thickness was reduced in RES lambs (0.11 ± 0.06; P ≤ 0.04) compared with CON (0.20 ± 0.06) and OVER (0.26 ± 0.06) lambs. Concentrations of IGF-I at 3 mo and IGFBP-3 from weaning (d 56 of age) to 3 mo of age tended to be greater ( P ≤ 0.06) in OVER lambs (334 ± 66 ng/mL and 175 ± 11 arbitrary units [AU], respectively) than CON lambs (149 ± 66 ng/mL and 140 ± 11 AU, respectively). At 3 mo, leptin was greater in OVER lambs compared with RES lambs (1.24 vs. 0.78 ± 0.13 ng/mL; P < 0.05). Over time, average insulin concentrations were greater in OVER and RES lambs than CON lambs (0.49 and 0.49 vs. 0.33 ± 0.05 ng/mL; P ≤ 0.02). However, concentrations of GH, IGFBP-2, glucose, triglycerides, and total cholesterol were not different ( P > 0.10) between treatment groups. During in vivo glucose tolerance test, baseline insulin concentrations were 68% and 85% greater ( P = 0.01), respectively, in RES and OVER lambs compared with CON lambs. Similarly, the glucose:insulin ratio was greater in RES and OVER lambs compared with CON lambs ( P = 0.01). Thus, in this experiment, poor maternal nutrition during gestation influenced body size, organ growth, fat accumulation, and concentrations of IGF-I, IGFBP-3, leptin, and insulin of offspring during the first 3 mo of age.